Proceedings of the 10th International Conference on Social Media and Society 2019
DOI: 10.1145/3328529.3328556
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Ease of Communication in Bipartite Social Endorsement Networks

Abstract: In this work, complex weighted bipartite social networks are developed to efficiently analyze, project and extract network knowledge. Specifically, to assess the overall ease of communication between the different network sub-clusters, a proper projection and measurement method is developed in which the defined measurement is a function of the network structure and preserves maximum relevant information. Using simulations, it is shown how the introduced measurement correlates with the concept of political pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
6
0
2
Order By: Relevance
“…In order to be able to establish sustainable guidelines and policies toward social media platforms that do not aim to prolong online time (addictive potential of social media), and to protect the individual from (potentially) detrimental aspects of social media use, such as being caught in the filter-bubble (Sindermann et al, 2020c ) and loss of privacy (Zuboff, 2015 ), it is of importance to (a) rethink the data business model (Sindermann et al, 2020d ) and (b) to understand exactly what a “good” or “healthy” social media platform might look like. It is of particular relevance that academic research and public policy work toward building of a social media architecture that does not endanger democratic processes (Shahrezaye et al, 2019 ; Papakyriakopoulos et al, 2020b ) or fosters sexism (Papakyriakopoulos et al, 2020a ), radicalization or “fake news” and conspiracy theories (Papakyriakopoulos et al, 2020b ). For example, the aforementioned problems around filter-bubbles and echo-chambers might be mitigated by excluding domains such as daily political news from news-feed personalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to be able to establish sustainable guidelines and policies toward social media platforms that do not aim to prolong online time (addictive potential of social media), and to protect the individual from (potentially) detrimental aspects of social media use, such as being caught in the filter-bubble (Sindermann et al, 2020c ) and loss of privacy (Zuboff, 2015 ), it is of importance to (a) rethink the data business model (Sindermann et al, 2020d ) and (b) to understand exactly what a “good” or “healthy” social media platform might look like. It is of particular relevance that academic research and public policy work toward building of a social media architecture that does not endanger democratic processes (Shahrezaye et al, 2019 ; Papakyriakopoulos et al, 2020b ) or fosters sexism (Papakyriakopoulos et al, 2020a ), radicalization or “fake news” and conspiracy theories (Papakyriakopoulos et al, 2020b ). For example, the aforementioned problems around filter-bubbles and echo-chambers might be mitigated by excluding domains such as daily political news from news-feed personalization.…”
Section: Discussionmentioning
confidence: 99%
“…They know what combination of design-elements on social media platforms (also in Freemium-games on smartphones) function best in attracting and keeping the attention of their users. They also possess better insights into human behavior guided by design elements such as a personalized news-feed, which is widely believed to be responsible for filter-bubbles (Pariser, 2011 ) and echo-chambers (Shahrezaye et al, 2019 ), but likely only in the case when users inform themselves about the daily political news exclusively via social media (Sindermann et al, 2020c ). Of note, personalized news-feeds are a good example to demonstrate how the addictive nature of social media and detrimental effects for society can be all linked to each other via a design-element and the data business model on social media.…”
Section: A Stronger Focus On the Data Business Model And Social Mediamentioning
confidence: 99%
“…This disjunction could be considered as a proxy for the polarization of German society. Indeed, Shahrezaye et al [64] reported that on Facebook the polarization between the AfD and the other political parties has increased in the last few years.…”
Section: Discussionmentioning
confidence: 99%
“…A set of investigations analyzes the behaviour of social groups under the algorithmic influence, to uncover the algorithmic impact on public opinion and behaviour (Pariser 2011;Bakshy et al 2015;Barberá et al 2015). Other studies investigate information diffusion and opinion formation (Yang 2016;Faris et al 2017;Stieglitz and Dang-Xuan 2013;Tufekci and Wilson 2012;Shahrezaye et al 2019), while others dedicate themselves to understanding properties of spreading misinformation by real or artificial users (Del Vicario et al 2016;Vosoughi et al 2018;Ferrara et al 2016;Papakyriakopoulos et al 2020). In social machines such as social media or search engines, political actors also explicitly use platform tools for political campaigning.…”
Section: Investigating Politics In Social Machinesmentioning
confidence: 99%